The Use of Glycomacropeptide in Dietary Management of Phenylketonuria - Osama K. Zaki; Lamia El-Wakeel; Yasmin Ebeid; Hanan S. Ez Elarab; Aisha Moustafa; Nayera Abdulazim; Hala Karara; Ahmed Elghawaby (Journal of Nutrition and Metabolism, 2016)
Dietary therapy is the most common therapy applied in treatment of Phenylketonuria (PKU) with restriction of intake of most natural proteins that are rich in Phenylalanine (Phe). Recently, it has been claimed that caseinoglycomacropeptide (GMP), derived of whey, may be used to replace the amino acid formulae (AAF). The Aim of Work. To study the feasibility of use of GMP for partial replacement of artificial formula in treatment of children with PKU. Methods. Ten patients with PKU were included in the study. They received the recommended daily allowances of protein in the form of AAF or a combination of AAF and GMP. The percent of intake of GMP in phases 1 and 2 was 50% and zero%, respectively. Results. The median and interquartiles of phenyl alanine Phe levels phase were not significantly different in phases I and II, 376 (167–551) μmol/L versus 490 (289–597) μmol/L, respectively. Phenylalanine/tyrosine ratio, amino acids, and other laboratory data showed no significant difference between the two phases. Conclusion. GMP may be used to replace 50% of the protein intake to improve the nutritive value and palatability of diet and to provide a more satisfactory diet. No toxicity or side effects were reported in patients on that regimen.